Contextual Processing and the Impacts of Aging and Neurodegeneration: A Scoping Review - Tran KH (Dove Medical Press, 2021)
Kim H Tran,1,2 Andrew P McDonald,1,3 Ryan CN D’Arcy,2,3 Xiaowei Song1,2 1Clinical Research Centre, Surrey Memorial Hospital, Fraser Health Authority, Surrey, BC, Canada; 2Department of Biomedical Physiology and Kinesiology, Simon Fraser University, Burnaby, BC, Canada; 3Department of Medicine, University of British Columbia, Vancouver, BC, CanadaCorrespondence: Xiaowei Song 13750 96th Avenue, Surrey, BC V3V 1Z2, CanadaTel +1 604 585 5666 ext. 774 986Email xiaowei.song@fraserhealth.caAbstract: Contextual processing (or context processing; CP) is an integral component of cognition. CP allows people to manage their thoughts and actions by adjusting to surroundings. CP involves the formation of an internal representation of context in relation to the environment, maintenance of this information over a period of time, and the updating of mental representations to reflect changes in the environment. Each of these functions can be affected by aging and associated conditions. Here, we introduced contextual processing research and summarized the literature studying the impact of normal aging and neurodegeneration-related cognitive decline on CP. Through searching the PubMed, PsycINFO, and Google Scholar databases, 23 studies were retrieved that focused on the impact of aging, mild cogniitve impairment (MCI), Alzheimer’s disease (AD), and Parkinson’s disease (PD) on CP. Results indicated that CP is particularly vulnerable to aging and neurodegeneration. Older adults had a delayed onset and reduced amplitude of electrophysiological response to information detection, comparison, and execution. MCI patients demonstrated clear signs of impaired CP compared to normal aging. The only study on AD suggested a decreased proactive control in AD participants in maintaining contextual information, but seemingly intact reactive control. Studies on PD restricted to non-demented older participants, who showed limited ability to use contextual information in cognitive and motor processes, exhibiting impaired reactive control but more or less intact proactive control. These data suggest that the decline in CP with age is further impacted by accelerated aging and neurodegeneration, providing insights for improving intervention strategies. This review highlights the need for increased attention to research this important but understudied field.Keywords: Alzheimer’s disease, Parkinson’s disease, mild-cognitive impairment, aging, dementia, contextual processing, EEG-ERP, behavior